Creating Narratives of Resilience and Connection through Histories of Urban Environmental Decline and Recovery: The West Boathouse Project. - Booij, Hanneke; Shearer, Ingrid (Scottish Historical Review, 2025)
This article explores how heritage organisations can leverage environmental histories to challenge and renegotiate perceptions of urban and environmental decline through practices of care with communities. Using Glasgow Building Preservation Trust's (GBPT) work on the Rejuvenation of the West Boathouse as a case study, we will examine how historical and environmental narratives were integrated into place-based and people-centred practices to address environmental challenges and encourage shifts in behaviours and attitudes. GBPT framed their mission and strategies in dialogue with notions of sustainability and resilience, connecting people with their local environment in the context of government and funding guidelines relating to sustainability and resilient communities. During the Rejuvenation of the West Boathouse at Glasgow Green, GBPT worked with environmental charities, local communities and primary schools. They challenged entrenched narratives of urban environmental decline and negative stereotypes about local communities through creative, participatory methods, co-producing new narratives of recovery and connection between people and the River Clyde. This article provides an original contribution to the emerging approaches to place-based practices in urban and blue spaces. This paper concludes that reconceptualising ideas of nature, culture and inclusion can support new narratives of recovery and resilience. These new narratives can strengthen social cohesion, foster a sense of place, and renew and reinforce community identity.